Variability analysis and empirical estimation of solar radiation at Ludhiana - Kingra, P.K. (Annals of Agricultural Research, 2018)
Solar radiation is one of the most important input components for agriculture. Both quality and quantity of solar radiation has a significant effect on crop productivity in any region. The two main plant physiological processes i.e. photosynthesis and transpiration are directly affected by solar radiation. Solar radiation in the wavelength range of 0.4 - 0.7 Î¼ is absorbed by the plants for the process of photosynthesis. Thus, the availability of accurate quantitative data of solar radiation is of paramount importance for conducting scientific studies on plant physiological processes and agricultural productivity. Such studies are difficult to conduct if accurate solar radiation data is not available. In the absence of trustworthy solar radiation data, empirical models for estimation of solar radiation from other climatological parameters especially sunshine hours, are indispensable. In the present investigation, solar radiation for Ludhiana was first computed from different weather parameters using CROPWAT model and then linear regression models were developed to estimate daily average solar radiation directly from sunshine hours data on monthly and annual basis. Trend analysis of mean annual solar radiation and sunshine hours indicated a decreasing trend (R2 = 0.39 and 0.41, respectively). Linear regression models were observed to estimate solar radiation in very good agreement with the solar radiation computed from CROPWAT model with R2 > 0.98 for all the months, which indicates that these models can be used very successfully for empirical estimation of solar radiation from sunshine hours during any period of the year under central Punjab conditions.